Correlation of atrial fibrillation and left atrial size in rheumatic mitral valve disease - Dorasanamma, Malli; Gangaram, U.; Karnati, Rajendra; Prasad, B. Indeevar (International Journal of Advances in Medicine, 2020)
Background: Atrial fibrillation (AF) is the most common sustained cardiac arrhythmia which is as associated with increased cardiovascular morbidity, mortality and preventable stroke. AF is common in rheumatic heart disease (RHD) particularly mitral stenosis (MS). Left atrial (LA) dilatation is the predisposing factor for the development of AF in rheumatic mitral valve disease. Aim was to study the correlation between AF and LA size in rheumatic mitral valve disease in the population of Southern Andhra Pradesh. Methods: This is a prospective, observational study conducted in 42 patients diagnosed to have RMVD in Narayana Medical College and Hospital, Nellore, Andhra Pradesh between August 2018 and July 2020. Detailed patient history and complete clinical examination were performed. Standard 12 lead Electrocardiography (ECG) and 2-D echocardiography were done. Left atrial size was measured and compared with patients in AF and with sinus rhythm. Results: The age of patients ranged from 20-76 years with the mean age of 40.33 years. Out of 42 patients 26 were in AF and 16 in sinus rhythm. Among 26 patients in AF, 22 (84.6%) had LA size ≥4 cm and 4 (15.38%) had <4 cm with mean LA size of 4.6 cm whereas among 16 patients in sinus rhythm, 10 (62.5%) had LA size <4 cm and 6 (37.5%) had ≥4 cm with a mean of 3.83 cm. Conclusions: Left atrial size ≥4 cm is the predisposing factor for the development of AF in rheumatic mitral valve disease. Therefore, if patients in sinus rhythm who are at high risk of developing AF are identified, prophylactic anticoagulation and antiarrythmic drugs might prevent AF induced complications like embolism and symptom exacerbation in rheumatic mitral valve disease.